Mother's Knowledge Level About Growth And Development With The Growing Development In Infants Aged 6-12 Months - Setiadi, Rocky; Angelina, Zenia; Warsanto, J. Alphonsus (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2020)
Introduction:Â The age of an infant is an essential age for growth. Its development is highspeed, follows a particular pattern, and varies between individual. An infant is still vulnerable to various health problems. The infant's development will be optimal if the mother's knowledge level is right and appropriate social interaction with the needs of the baby at its development stage. Purpose: This study aims to analyze the relationship between mother's knowledge levels about growth development with the compatibility of growing development in infants aged 612 months. Method: This study used an observational analytic method with a cross-sectional design. Statistical analysis used the Chi-Square test to determine the correlation followed by a contingency coefficient. Samples were taken according to the criteria of age 6-12 months as much as 55 respondents. data on the mother's knowledge level was collected using a questionnaire. The research evaluate growth using a baby scale of height, weight, head circumference, and to evaluate development progress using a prescreening developmental questionnaire (KPSP). This study was conducted on July 5 - August 1, 2019, at the Gotong Royong Pratama Clinic in Surabaya. Results: The relationship of mother's knowledge level about growth development with the compatibility of growing development in infants aged 6-12 months obtained significant results with a p-value of p = 0,000 (p <0.05). Contingency coefficient test results with a value of 0.436 which shows that the strength of the relationship is strong enough. the relationshipbetween mother's knowledge level about growing development with the compatibility ofgrowing development in infants aged 6-12 months obtained significant results with a p-valueof p = 0.007 (p <0.05 ). Contingency coefficient test results with a value of 0,343, whichshows that the strength of the relationship is strong enough. Conclusion: There is a significant relationship between the mother's knowledge levels about growing development with the compatibility of growing development in infants aged 6-12 months